1989
DOI: 10.1063/1.101137
|View full text |Cite
|
Sign up to set email alerts
|

Strain variations in heteroepitaxial InP-on-Si grown by low-pressure metalorganic chemical vapor deposition

Abstract: Variations in the magnitude and sign of the strain in epitaxial InP directly on (001) Si are studied as a function of layer thickness using photoluminescence and x-ray diffraction techniques. The heteroepilayers were grown by low-pressure metalorganic chemical vapor deposition and showed good quality. We find that biaxial compressive strains are still present in InP layers with thickness up to 0.8 μm. The magnitudes of compressive strains are much larger than those expected from the equilibrium theory. With in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Good layers are obtained by using the so-called two-step method. In this method, first a thin buffer layer (also known as the first layer, thickness 30 nm to 0.2 µm) is grown at a low temperature, in the range 300 to 450 • C. The second layer, several microns thick, is grown on the buffer layer at higher temperatures (∼ 600 • C) generally used in homoepitaxy [130,136,142] (and references given in these papers). Lattice mismatch is approximately 4% for GaAs/Si, 0.4% for GaP/Si and 8% for InP/Si (see table 1).…”
Section: Thermal Stress and Strainmentioning
confidence: 99%
See 3 more Smart Citations
“…Good layers are obtained by using the so-called two-step method. In this method, first a thin buffer layer (also known as the first layer, thickness 30 nm to 0.2 µm) is grown at a low temperature, in the range 300 to 450 • C. The second layer, several microns thick, is grown on the buffer layer at higher temperatures (∼ 600 • C) generally used in homoepitaxy [130,136,142] (and references given in these papers). Lattice mismatch is approximately 4% for GaAs/Si, 0.4% for GaP/Si and 8% for InP/Si (see table 1).…”
Section: Thermal Stress and Strainmentioning
confidence: 99%
“…The thickness of the layer at which transition from compression to tension takes place depends on the III-V semiconductor being grown and on the growth and annealing temperatures. For GaAs and InP it varies from 0.1 to 1 µm [9,42,130,136,142]. The work done on GaP is not so extensive; Yamamoto et al [142] have observed the transition at about 1 µm.…”
Section: Thermal Stress and Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleation problem for GaN onto these materials is particularly severe because of a low incorporation efficiency of the metal-organic precursors typically used for growth. 5 Several approaches have previously been developed for suppressing three-dimensional growth, including lowtemperature buffer layers, [6][7][8] adsorbed foreign surface species ͑i.e., surfactants͒, 9,10 and low-energy ion-assisted growth. 11 Of these approaches, ion-assisted growth has received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%